1997
DOI: 10.1007/s004410050845
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the distribution of glycoconjugates in the digestive gland of the bivalve mollusc Mytilus galloprovincialis by conventional and lectin histochemistry

Abstract: We examined the distribution and pattern of reactivity of a panel of 16 lectins in the digestive gland of the bivalve mollusc Mytilus galloprovincialis at the light-microscopic level. Various chemical treatments were applied in combination with lectins to differentiate between N- and O-linked oligosaccharides. Several control reactions were carried out, including replacement of lectins by buffer and incubation with their specific competitive inhibitors. Some lectins reacted selectively with particular cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
3
14
0
4
Order By: Relevance
“…If terminal GalNAc residues are present in some O-glycoproteins, they are not attached directly to the serine residue, as evidenced by the absence of VVL binding (Tollefsen and Kornfeld, 1983). Concerning the fucose (Fuc) residues, the UEA I binding could indicate the presence of terminal Fuc residues outside of the inner core of N-glycoproteins (Baldus et al, 1996;Robledo et al, 1997). On the other hand, AAL binding could indicate the presence in some N-glycoproteins of a terminal Fuc with an ␣1,6 link to the GlcNAc involved in the N-glycosylamine linkage (Debray and Montreuil, 1989).…”
Section: Saccharide Composition Of the Intrastereomic Organic Matrixmentioning
confidence: 95%
See 1 more Smart Citation
“…If terminal GalNAc residues are present in some O-glycoproteins, they are not attached directly to the serine residue, as evidenced by the absence of VVL binding (Tollefsen and Kornfeld, 1983). Concerning the fucose (Fuc) residues, the UEA I binding could indicate the presence of terminal Fuc residues outside of the inner core of N-glycoproteins (Baldus et al, 1996;Robledo et al, 1997). On the other hand, AAL binding could indicate the presence in some N-glycoproteins of a terminal Fuc with an ␣1,6 link to the GlcNAc involved in the N-glycosylamine linkage (Debray and Montreuil, 1989).…”
Section: Saccharide Composition Of the Intrastereomic Organic Matrixmentioning
confidence: 95%
“…The PHA-E and PHA-L bindings to the IOM demonstrate, in the matrix, the presence of bisected bi-or tri-antennary complex chains and of tri-or tetra-antennary complex chains, respectively (Cummings and Kornfeld, 1982;Hammarström et al, 1982;Liener et al, 1986). Con A binding to the IOM could indicate the presence of high-mannose-type N-glycoproteins or of biantennary complex N-glycoproteins (Lampreave et al, 1995) although it was also recently shown to react with O-glycoproteins (Robledo et al, 1997).…”
Section: Saccharide Composition Of the Intrastereomic Organic Matrixmentioning
confidence: 98%
“…In addition, a second control series was made for AcPase activity by adding a specific inhibitor (10 mM NaFl) to the complete incubation solution. Based on a previous study of mussel digestive gland tissue at the light-microscope level, in which 16 lectins (including chemical and enzymatic treatments, such as desulphation, β-elimination, treatment with endo-F enzyme and their combination) were employed (Robledo et al 1997), seven lectins that bound to digestive cells were selected for the present investigation (Table 1). The concentrations used in each case depended on the technical approach used (preembedding and post-embedding) and appear detailed in Tables 3 and 4.…”
Section: Enzyme Cytochemistry Of Acid Hydrolasesmentioning
confidence: 99%
“…Based on these results, seven lectins (see Table 1) have been selected for the present study in order to examine the five saccharide residues found in mussel digestive cells: fucose, galactose, mannose, Nacetylglucosamine (GlcNAc) and N-acetylgalactosamine (GalNAc). According to Robledo et al (1997), the binding of lectins to sialic acid is absent or weak in the mussel digestive gland, even after desulphation and chemical or enzymatic digestion; therefore, lectins able to recognize sialic acid residues have been omitted from the present investigation. Likewise, several other agglutinin types, e.g.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation